Bizonyítási tilalmak a magyar büntetőeljárásban a törvénysértő (jogellenes) bizonyítékok kizárása - Gácsi Anett Erzsébet (Szegedi Tudományegyetem Állam- és Jogtudományi Kar Szeged, 2012)
The issue of the prohibitions of proof is still significantly important - as professor Ervin Cséka said it is considered to be "evergreen" - within the doctrine of proof. The prohibitions of proof (or in other words the rules excluding the taking of evidence) shall be considered as a generic term. Therefore these prohibitions can refer to the subject of proof (certain facts on which evidence taking cannot be conducted), to the means of proof or to the manner of proof. Taking of evidence by the violation of these prohibitions result in unlawful evidences which shall be excluded from the circle of evidences in order to maintain the fairness of the procedure. This requirement is stated in Paragraph 4 of Article 78 of the operative Code of Criminal Procedure (Act XIX of 1998): "No fact received from any means of proof shall be considered as an evidence which has taken by the judge, the prosecution or the investigation authority by committing a crime or by any other unlawful manner or by limiting the fundamental procedural rights of the procedure's participants." This rule is not only inaccurate but it leaves numerous questions unanswered and the solution has been always the task of the judicial practice. The study respectfully written for the 90' birthday of professor emeritus Ervin Cséka is focusing on the exclusion of evidences taken unlawfully and it introduces this issue by theoretical arguments along with the relating judicial practice with its 60 decisions between 2007 and 2011.
Keywords: Társadalomtudományok; Jogtudomány